A case-matched comparison and meta-analysis comparing pylorus-resecting pancreaticoduodenectomy with pylorus-preserving pancreaticoduodenectomy for the incidence of postoperative delayed gastric emptying - Zhou, Yanming (HPB (Oxford), 2015)
OBJECTIVES: This study was conducted to compare the incidences of delayed gastric emptying (DGE) following pylorus-resecting pancreaticoduodenectomy (PrPD) and pylorus-preserving pancreaticoduodenectomy (PpPD), respectively. METHODS: Data for 37 patients submitted to PrPD were compared with data for a matched number of patients submitted to PpPD during the same period. A meta-analysis of comparative studies of the two techniques was also carried out. The primary endpoint was the rate of DGE (grades A–C) defined according to the International Study Group of Pancreatic Surgery criteria. RESULTS: In the case-matched comparison, both overall DGE (six PrPD patients and 17 PpPD patients; P = 0.006) and clinically relevant DGE (one PrPD and eight PpPD patients; P = 0.013) occurred significantly less often in the PrPD group than in the PpPD group. Based on eight non-randomized clinical trials and two randomized clinical trials involving 804 subjects, the meta-analysis further confirmed a significant reduction in DGE with pooled odds ratios of 0.33 [95% confidence interval (CI) 0.17–0.63; P < 0.001] and 0.13 (95% CI 0.05–0.40; P < 0.001) for overall DGE and clinically relevant DGE, respectively. Other complications and mortality were similar in both groups. CONCLUSIONS: Pylorus-resecting pancreaticoduodenectomy is a safe procedure associated with less severe and less frequent postoperative DGE than PpPD.